Oscillatory Properties of Functional Connections Between Sensory Areas Mediate Cross-Modal Illusory Perception - Cooke, Jason (J Neurosci, 2019)
The presentation of simple auditory stimuli can significantly impact visual processing and even induce visual illusions, such as the auditory-induced double flash illusion (DFI). These cross-modal processes have been shown to be driven by occipital oscillatory activity within the alpha band. Whether this phenomenon is network specific or can be generalized to other sensory interactions remains unknown. The aim of the current study was to test whether cross-modal interactions between somatosensory-to-visual areas leading to the same (but tactile-induced) DFI share similar properties with the auditory DFI. We hypothesized that if the effects are mediated by the oscillatory properties of early visual areas per se, then the two versions of the illusion should be subtended by the same neurophysiological mechanism (i.e., the speed of the alpha frequency). Alternatively, if the oscillatory activity in visual areas predicting this phenomenon is dependent on the specific neural network involved, then it should reflect network-specific oscillatory properties. In line with the latter, results recorded in humans (both sexes) show a network-specific oscillatory profile linking the auditory DFI to occipital alpha oscillations, replicating previous findings, and tactile DFI to occipital beta oscillations, a rhythm typical of somatosensory processes. These frequency-specific effects are observed for visual (but not auditory or somatosensory) areas and account for auditory–visual connectivity in the alpha band and somatosensory–visual connectivity in the beta band. We conclude that task-dependent visual oscillations reflect network-specific oscillatory properties favoring optimal directional neural communication timing for sensory binding. SIGNIFICANCE STATEMENT We investigated the oscillatory correlates of the auditory- and tactile-induced double flash illusion (DFI), a phenomenon where two interleaved beeps (taps) set within 100 ms apart and paired with one visual flash induce the sensation of a second illusory flash. Results confirm previous evidence that the speed of individual occipital alpha oscillations predict the temporal window of the auditory-induced illusion. Importantly, they provide novel evidence that the tactile-induced DFI is instead mediated by the speed of individual occipital beta oscillations. These task-dependent occipital oscillations are shown to be mediated by the oscillatory properties of the neural network engaged in the task to favor optimal temporal integration between the senses.